Beautiful at all seasons : southern gardening and beyond with Elizabeth Lawrence - Lawrence, Elizabeth, 1904-1985 (E-Duke books scholarly collection., 2007)
A collection of gardening columns by Elizabeth Lawrence that were published in her column ""The Garden Gate"" which appeared weekly in the Charlotte Observer.